2014
DOI: 10.1007/s00586-014-3456-y
|View full text |Cite
|
Sign up to set email alerts
|

The influence of cervical plate fixation with either autologous bone or cage insertion on radiographic and patient-rated outcomes after two-level anterior cervical discectomy and fusion

Abstract: PURPOSE We aimed to identify technique-related factors influencing radiographic and patientrated outcomes after two-level anterior cervical discectomy with fusion (ACDF) using either cage or autologous bone, with or without anterior plate fixation (APF). METHODS This single center study was nested within the Eurospine Spine Tango data acquisition system. INCLUSION CRITERIA consecutive two-level ACDF patients (2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012) presenting with signs of degenerative cervical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…We previously reported that ACDF with plating had better radiologic outcome than stand-alone cage groups 13) . In that study, we suggested that anterior plating may play a key role in the support of anterior inter-body height 2) . However, not a few studies have mentioned ACDF with SAC is a clinically/radiologically satisfactory procedure 11 16 17 18) .…”
Section: Introductionmentioning
confidence: 83%
“…We previously reported that ACDF with plating had better radiologic outcome than stand-alone cage groups 13) . In that study, we suggested that anterior plating may play a key role in the support of anterior inter-body height 2) . However, not a few studies have mentioned ACDF with SAC is a clinically/radiologically satisfactory procedure 11 16 17 18) .…”
Section: Introductionmentioning
confidence: 83%
“…The relationships between the demographic data and radiologic/clinical outcome had no statistical significance. Previous literature demonstrated that gender, age, level of surgery, cage height and BMD had no significance as outcome factors of the ACDFI surgery [1,2] .…”
Section: Discussionmentioning
confidence: 99%
“…This procedure involved removing the symptomatic disc from an anterior approach without placement of a bone graft. Early studies demonstrated fusion rates with Anterior Cervical Discectomy (ACD) were similar to those of procedures of anterior cervical discectomy and fusion (ACDF) using bone graft [1,2,15] . This extra step has been proposed to promote bony fusion maximizing stability and maintaining 1927 disc space height reducing risk of foraminal stenosis.…”
Section: Introductionmentioning
confidence: 99%
“…Standalone strut graft has high rate of complications such as graft subsidence, dislodgement, non-union and donor site morbidities. Anterior plating has inherent deficiencies like plate loosening, screw pullout, breakage, trachea-oesophagal irritation has increased operation time [2,3] . Intervertebral cages have been postulated to avoid some of these difficulties due to their selffixing construct, ability to contain graft or graft substitute in it.…”
Section: Introductionmentioning
confidence: 99%